PENGARUH SIFAT PSIKOLOGIS KONSUMENTERHADAP PEMBELIAN KOMPULSIF (Studi Terhadap Mahasiswa Universitas Mayjen Sungkono Mojokerto) - Adil Abdilah (Universitas Tribhuwana Tunggadewi, 2017)
Development of the theory of consumer behavior found any part of the bad side of consumer shopping behavior. Such behavior is compulsive buying. This research study is a replication of Johnson and Attman (2009). Researchers wanted to prove a pattern of relationships variable used in the study, applied in Indonesia. The problem of this research is whether there is a significant difference in the relationship pattern between variables or the same, where there is a difference of background between this research and previous research. The method used in this study is the path analysis, using 100 respondents from Mayjen Sungkono University students of Mojokerto. Research shows that all paths are significant positive and it can be concluded that the direct influence of the tendency of neuroticism, materialism, and orientation to the fashion of compulsive buying and indirect effect on compulsive buying through materialism and fashion orientation. Thusmaterialism and fashion orientation to reinforce the tendency toward neuroticism compulsive buying behavior.